Challenges of data availability: Analysing the water-energy nexus in electricity generation. (November 2019) - Larsen, M.A.D.; Petrovic, S.; Engström, R.E.; Drews, M.; Liersch, S.; Karlsson, K.B.; Howells, M.
Abstract: Water is paramount for the operation of energy systems, for securing food supply and for the industry and municipalities. Intersectoral competition for water resources can negatively affect water scarce regions by e.g. power plants shutdowns, poor agricultural yields, and lack of potable water. Future economic and population growth as well as climate change is likely to exacerbate these patterns. However, models used for energy system management and planning in general do not properly include water availability which can lead to improper representations of water-energy interlinkages. The paper initially highlights the water usage rates of current technologies within electricity generation and technologies with a potential to reduce water usage, electricity consumption or GHG emissions. Secondly, the paper presents currently available data on current and future projected water resources as well as data on energy statistics relevant to water-energy nexus studies. Thirdly, implementation cases are presented showing examples of water-energy nexus studies for the data presented. Finally, the paper highlights main challenges in studying the linkage between water and energy. We find a substantial gap in the general availability and quality of regional and global data for detailed quantitative analyses and also identify a need for standardization of formats and data collection methodologies across data and disciplines. An effort towards a coordinated, and sustained open-access data framework with energy sector water usage at fine spatio-temporal scales alongside hydro-climatic observation and model data using common forcings and scenarios for future projections (of climate, socio-economy and technology) is therefore recommended for future water-energy nexus studies. Highlights: Detailed and available data on energy sector water use is generally unavailable. Current data do not support a full integration of energy and water for management. Future data improvements must include standardization, accessibility and high detail. A coordinated and sustained open-access data framework is recommended.